Adat Ulu Azm Min Al-Rusul fi Hayatihim al-Ijtimaiyah Min Khilal Al-Quran wa Al-Sunah: The Practices of the Prophets of Ulu al Azm in Their Social Life Through the Quran and Sunnah - Fadhli Ananda; Saadeldin Mansour Gasmelsid; Ahmad El-Mogtaba Bannga Ahmed Ali (Studia Quranika, 2025)
The Messengers of Ulu al-Azm were distinguished Prophets who held high positions and exerted significant influence in their societies. they shared similar Practices and approaches in addressing challenges in their social lives. Their determination and patience in improving the community is seen in the Qur'an and Sunnah. So this research seeks to uncover the habits of Ulu al-Azm in their social life and reveal the meanings contained therein based on the verses of the Qur'an and Hadith. This research uses the descriptive method of analysis to look at the habits in social life experienced by the Ulu al-Azmi prophets. Among the conclusions of this study is that the Apostle Ulu al-Azm both have noble morals, because the Apostle Ulu al-Azm applies social values that are guided by Allah Ta'ala, as for the differences in times and social conditions experienced by the Apostle Ulu al-Azm are different but if there are causes and characteristics that are repeated they will use the same approach in improving and restoring social values in their society, because all social values and the ultimate criteria for good and bad social behavior are rooted in divine revelation.